Exosomes: emerging roles in communication between blood cells and vascular tissues during atherosclerosis. Issue 5 (October 2015) - Huber, Heinrich J.; Holvoet, Paul
Abstract : Purpose of review: Microvesicles, in general, and exosomes together with their delivered content in particular, are now being widely recognized as key players in atherosclerosis. We have previously reviewed the role of microvesicles in atherosclerosis pathogenesis, diagnosis and therapy. Here, we focus on the roles of exosomes and discuss their emergent role in mediating activation and response to inflammation, vessel infiltration and induction of coagulation. We will finally give an outlook to discuss novel detection techniques and systems biology based data analyses to investigate exosome-mediated cell-to-cell communication. Recent findings: Recent research points to a role of exosomes in delivering apoptotic and inflammatory content between blood cells and vascular cells, with a potential contribution of exosomes secreted by adipose tissue. An atheroprotective role of exosomes in response to coagulation that may contrast with the procoagulatory role of platelet-derived larger microvesicles is envisaged. New detection and separation methods and systems biology techniques are emerging. Conclusion: We project that the development of novel detection, separation and analysis mechanism and systems-based analysis methods will further unravel the paracrine and endocrine 'communication protocol' between cellular players in atherosclerosis, mediating inflammation, oxidative stress and apoptosis.